Odpowiedzi

2009-12-21T22:23:43+01:00
A) 3x - 6/5 = 4x + 12/3
3x - 30 = 4x + 36
3x - 4x = 36 + 36
-x =72

b) (x-4) - 1 = (x-3)(x-2)
x - 4 - 1 = 2x + 6
x-2x = 6 + 4 + 1
x = 11

c)= 1,5 - x - 6 + 3x -16 = 0
-x +3x = 0 - 1,5 + 6 + 16
2x = -1,5 + 6 + 16
2x = 4,5 + 16
2x = 20,5
2009-12-21T22:28:33+01:00
A) 3(x-2)/5 = 4(x+3)/3
(3x-6)/5=4x+12/3
5(4x+3)=3(3x-2)
20x+15=9x-6
20x-9x=-6-15
11x=-21/:11
x=-21/11

b) (x-4)-1= (x-3)(x-2)
(x-4)-1=x²-2x-3x+6
x+4-1=x²-2x-3x+6
x+2x+3x-x²=6-4+1
6x-x²=3
nie wiem pogubiłam sie..

c) 1,5 - x-1/6 + 3x-2/8 =0
1,5-x-1/6+3x-2/8=0/*48
8(1,5-x-1)+6(3x-2)=0
12-8x-8+18x-12=0
-8x+18x=12+8-12
10x=8/10
x=8/10=4/5